Tanend appèl: De bijdrage van ontkerkelijking en ontzuiling aan het aantal CDA-zetels in de Tweede Kamer, 1970-2010 - te Grotenhuis, Manfred; Eisinga, Rob; van der Meer, Tom; Pelzer, Ben (Religie & Samenleving, 2012)
In this article we raise the research question to what extent the declining number of church members and the changing voting behavior among church members and non-members explain the longitudinal trend in voter turnout of the largest Christian political party in the Netherlands, the Christian Democratic Appeal (CDA). In a counterfactual analysis we simulated no disaffiliation since 1970 and found a more or less constant loss of 9 seats in the Dutch House of Representatives throughout the whole period. Next, we simulated no change in voting behavior of both church members and non-members since 1970 and this resulted in a substantial loss of 10 to 14 seats, concentrated in 1994-2010. We also estimated the contribution of church members’ and non-members’ voting behavior separately. It turned out that until 1994 the effects were opposite to each other. As a result the net effect of voting behavior was close to zero for a long time. This changed dramatically from the 1994 elections onwards as many church members did not vote for the CDA anymore and tipped the balance. This was especially so in the 2010 elections, where the CDA faced unprecedented losses.